Electrochemical impedance study of iron electrodes covered by polypyrrole films electrosynthesized in the presence of AOT - Lehr, Ivana Leticia (2008)
The electrosynthesis of polypyrrole (PPy) onto iron electrodes in the presence of sodium bis(2-ethylhexyl) sulfosuccinate (AOT) solutions is characterized by the formation of a gelatinous material in parallel to the growth of the polymer. The electrochemical behaviour of this system under different experimental conditions was investigated using electrochemical impedance spectroscopy (EIS) and cyclic voltammetry. The study was focused in understanding the effects of various parameters, such as nature of the electrolyte and film thickness, on the dissolution process of iron. The response at low frequencies is related with the activity of the substrate. It was found that the electrode impedance for thick films is governed by diffusion of iron ions across the polymer and gel-like layers. Mass transfer contribution is prominent at the early stages of corrosion in chloride solution.